ANALISIS PENGARUH KEDALAMAN POTONG DAN VARIASI CAMPURAN DROMUS TERHADAP KEKASARAN PERMUKAAN BAJA AISI 1045 SETELAH DIQUENCHING MENGGUNAKAN AIR LAUT - Odidio Pratama Odidio; Zaldy Kurniawan; Eko Yudo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Grinding is done to remove the remnants of the uneven machining process to produce a flat, smooth surface and get the desired accuracy. The research that has been conducted aims to determine the effect of variations in depth of cut and variations in dromus mixture on the surface roughness of AISI 1045 steel material after quenching and a good dromus mixture for flat grinding processes. The method in this research is experimental. The depth of cut variations given are 0.015mm, 0.020mm, 0.025mm and the mixed dromus variations are 1:10, 1:15 and 1:20. The results of this study with a depth of cut of 0.015mm with a mixture of dromus 1:10, 1:15, 1:20 get the results of 0.228µm, 0.151µm, and 0.107µm. A depth of cut of 0.020mm with a mixture of 1:10, 1:15, 1:20 dromus resulted in 0.220µm, 0.205µm, and 0.155µm. A depth of cut of 0.025mm with a mixture of 1:10, 1:15, 1:20 dromus yields 0.268µm, 0.214µm, and 0.155µm. The roughness value obtained increased with increasing the depth of the cuts made, but decreased if the dromus mixture was getting dilute.